Microsurgical reconstruction of the skull base and midface after orbitomaxillary resections for malignant tumors - M. V. Bolotin; A. M. Mudunov; V. A. Sobolevsky; I. M. Gelfand; I. V. Orlova; A. A. Akhundov (Сибирский онкологический журнал)
Background. Orbitomaxillary resection includes exenteration of the orbital contents with resection of the inferior orbital and medial walls. The main goals are: reconstruction of soft tissue and bone structure defects, tamponade of the orbital cavity and/or its preparation for further ocular prosthetics, and reconstruction of the skull base defect. The purpose of the study to present the immediate results of orbitomaxillary resections in patients with malignant neoplasms of the skull base and midface. Material and methods. Between 2014 and 2020, 6 patients who previously underwent surgery for primary cancer (n=3) and recurrent cancer (n=3) were treated at the Head and Neck cancer department of N.N. Blokhin National medical Research center of oncology. To reconstruct defects after resection of bone structures (maxilla, frontal and nasal bones) and skin, a musculocutaneous alt-flap was used in 3 (50 %) cases and a fascial skin radial flap in 3 (50 %) cases. Results. The aesthetic result was assessed in 6 patients. In all cases, a satisfactory result was obtained. None of the patients who underwent resection of the dura mater followed by reconstruction had no symptoms of liquorrhea in the postoperative period. Conclusion. Flap selection depends on the defect size. In cases with a small defect size (up to 70 cm3), reconstruction with the radial fascial skin flap can be performed. If the defect size is more than 71 cm3, reconstruction with musculocutaneous alt flap can be the method of choice.